STUDI KOMPARATIF KONSEP MAQASHID SYARIAH IMAM AS-SHATIBI DENGAN THE HIRARCHY OF HUMAN NEEDS ABRAHAM MASLOW - Saniah, Nur; Nasution, Liantha Adam (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Way to understand human nature is to approach that is more directed to the theory of human needs. Today there has been a lot of research accomplished by psychologists in an effort to compile a theory of human needs. In Islam, Allah has regulated and made the Qur'an a guideline for human life, including matters relating to human needs. This research is a qualitative research with descriptive analysis and content analysis, which compares the concept of maqashid syariah and Abraham Maslow's The Hierarchy Of Human Needs and describes the proper interpretation of the text. Maqshid sharia and The Hierarchy of Human Needs are levels of human needs from two different perspectives of human needs. The results of the study concluded that maqashid sharia was formulated with the main considerations in accordance with God's purpose in passing down syari'at to humans so that they behave in accordance with the norms that He sent down and to maintain the benefit of humans in this world and the hereafter. Whereas in formulating The Hierarchy of Human Needs, Maslow was influenced by the philosophy of humanism which was detached from religious (secular) frames. Maslow's hierarchy of needs did not include The spiritual needs or religious motives (the need for religion) into the theory of the hierarchy of human needs.